Faktizität und Gebrauch früher Fotografie - factuality and utilization of early photography: Internationale Tagung der Fototheken des Deutschen Archäologischen Instituts Rom und der Bibliotheca Hertziana - Max-Planck-Institut für Kunstgeschichte, 22.-24. März 2017 - Bartsch, Tatjana; Bockmann, Ralf; Pasieka, Paul; Röll, Johannes (Beiträge zur Geschichte der Archäologie und der Altertumswissenschaften, 2021)
One of the essential characteristics of photography is the diversity of its manifestations. As a flexible medium, it can be adapted to new historical, cultural or aesthetic circumstances. Photographs are encountered as material artefacts, such as exposed metal plates or enlargements on photographic paper, as well as immaterial projections or digital recordings. Especially in the early days, there was an incomparable wealth of variations in recording techniques and reproduction processes, which were specified and differentiated according to the respective intended use.The conference volume is dedicated to the cross-disciplinary relationship between the factuality of photographs in the sense of their individual, material constitution and their presentation and usage contexts from the second half of the 19th to the beginning of the 20th century